Modern condition and tendencies of innovative development of megapolis (Journal of Economic Research & Business Administration, 2018)
The development of innovation activities in Kazakhstan will be more effective if the regions begin to intensify their activities in this direction. The development of the city is greatly influenced by the level of innovation activity. The article presents an analysis of the development of innovation activities in the metropolis – the city of Almaty. This article analyzes literary sources, which allowed to understand the features of innovation. The authors noted the importance and importance of innovation. The article assesses the level of development of innovation activity in the metropolis in the dynamics, changes in the activity and sources of financing of innovations, identifies structural changes in the sectors and areas of activity. Studies of the main indicators of the degree of development of innovative activity and the factors hindering their development were conducted. For the analysis, a study was conducted in the form ofa survey of experts and in-depth interviews in the field and innovation. The study concluded that the developmentof innovation requires an integrated approach, aimed not only at generating innovations, butalso stimulating enterprises that not only develop innovations, but produce and market new products.